Occupational stressors among workers in a cotton ginning factory in Burkina Faso - Traore , I; Traore , TI; Kabore , NF; Sanon/Lompo , MS; Ouedraogo , AF; Kabore , SG; Zabre , A; Namoulniara Diatto , C; Compaore , A; Sawadogo , GLB (HEALTH SCIENCES AND DISEASE, 2022)
Introduction. Occupational stress is recognized throughout the world as a real public health problem. Several factors are associated with its occurrence in workers. Objective. The objective of the study was to determine stress factors among workers in a cotton ginning factory in Burkina Faso. Material and method. This was an analytical cross-sectional study that took place from November 10, 2021 to June 29, 2022 in a cotton ginning factory in Burkina Faso. We conducted a convenience sample. Factors associated with stress were investigated using logistic regression. Results. A total of 192 workers were included in the study. The average age was 43,91 ± 7,03 years, the sex ratio of 191 men for one woman. 106 workers (55,21%) had secondary or higher education. 53 workers (27,60) were technicians. 115 (or 60%) worked in a shift system and 172 workers (or 89,58%) worked an average of 8 hours a day. The factors associated with stress were the low level of school education (p<0,001), the type of contract, the professional category, the organization of working hours and the workstation (p=0,008). Conclusion. The study carried out in the cotton ginning sector noted factors associated with the occurrence of stress among workers. Taking these different risk factors into account in stress prevention actions would improve worker health.